Pengaruh Waktu Tinggal Hidrolik Terhadap Efisiensi Penyisihan Padatan Dalam Limbah Cair Industri Sagu Dengan Menggunakan Bioreaktor Hibrid Anaerob Dua Tahap - Riki Rahmadhan; Adrianto Ahmad; Ahmad Fadli (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Sagoo industries was produced wastewater with high concentration of solids that potentially causes environment problem’s. One way to got lower concentration of solids with making use two-stage hybrid anaerobic bioreactor’s with stone media. The purpose of this study was to remove and determine the highest solids removal efficiency in wastewater treatment sagoo. Twosatge hybrid anaerobic bioreactor in continuous process with working volumes 10 L was used instage I and 20 L was used in stage II. The output from stage I was used as the input for stage II. The two-stage reactor was operated at a hydraulic retention time that varied from 2 days in stage I and 3,5 and 7 days in stage II. The results showed that highest of solids removal efficiency was obtained in the operation of hydraulic retention time 7 days. The value of TS(81,03%), TVS (72,92%), TSS (71,13%) and VSS (68,63%). Two-stage hybrid anaerobic bioreactors system exactly effective and efficient within to got lower concentration of solids in wastewater of sagoo industry’s.Keywords: anaerobic, continuous, hybrid bioreactor, hydraulic retention time, solid concentrations, two-stage, wastewater of sagoo industry.